Insights on Universal Pension Scheme in Bangladesh: Trajectory or Deviation - Faeique, Azmaine; Shaulin, Nahida; Naoar Siena, Jannateen; Ahmed Roza, Meherin; Tahmeed Abdullah, Mohammad (Department of Government Studies, Universitas Syiah Kuala, 2024)
The Universal Pension Scheme (UPS) is a fairly new policy by the Bangladesh government, inaugurated on 17th August 2023, aiming at giving the nation's aging population a monthly stipend and placing them under a well-organized social safety net program. This study aimed to find out the perception of the people regarding the UPS and the challenges that beset with this perception. The study uses a quantitative method to collect data from 404 participants through a close ended questionnaire following simple random sampling. The SPSS software was used to analyze the data for chi-square testing, cross tabulation, and descriptive statistics. By conducting the Chi-square test (p0.05), the overall results of the study revealed that the general people are not much willing to participate in the Universal Pension Scheme despite knowing about it. Though many still do not properly understand the different schemes of the UPS and prefer the traditional and familiar banking procedure for saving money, many mainly refrain from agreeing to participate on it because of the risk of inflation and regime change. Thus, most people prefer investing in a business to make profit and be free from these risks that are associated with UPS.